Polio inactivated vaccine costs into routine childhood immunization in Brazil - Sartori, Ana Marli Christovam; Vicentine, Margarete Paganotti; Gryninger, Lígia Castelloni Figueiredo; Soárez, Patricia Coelho de; Novaes, Hillegonda Maria Dutilh (Revista de Saúde Pública, 2015)
OBJECTIVE To analyze the costs of vaccination regimens for introducing inactivated polio vaccine in routine immunization in Brazil.METHODS A cost analysis was conducted for vaccines in five vaccination regimens, including inactivated polio vaccine, compared with the oral polio vaccine-only regimen. The costs of the vaccines were estimated for routine use and for the “National Immunization Days”, during when the oral polio vaccine is administered to children aged less than five years, independent of their vaccine status, and the strategic stock of inactivated polio vaccine. The presented estimated costs are of 2011.RESULTS The annual costs of the oral vaccine-only program (routine and two National Immunization Days) were estimated at US$19,873,170. The incremental costs of inclusion of the inactivated vaccine depended on the number of vaccine doses, presentation of the vaccine (bottles with single dose or ten doses), and number of “National Immunization Days” carried out. The cost of the regimen adopted with two doses of inactivated vaccine followed by three doses of oral vaccine and one “National Immunization Day” was estimated at US$29,653,539. The concomitant replacement of the DTPw/Hib and HepB vaccines with the pentavalent vaccine enabled the introduction of the inactivated polio without increasing the number of injections or number of visits needed to complete the vaccination.CONCLUSIONS The introduction of the inactivated vaccine increased the annual costs of the polio vaccines by 49.2% compared with the oral vaccine-only regimen. This increase represented 1.13% of the expenditure of the National Immunization Program on the purchase of vaccines in 2011.